A multiple linear regression analysis of factors affecting the simulated Basic Life Support (BLS) performance with Automated External Defibrillator (AED) in Flemish lifeguards. (April 2015) - Iserbyt, Peter; Schouppe, Gilles; Charlier, Nathalie
Abstract: Background: Research investigating lifeguards' performance of Basic Life Support (BLS) with Automated External Defibrillator (AED) is limited. Aim: Assessing simulated BLS/AED performance in Flemish lifeguards and identifying factors affecting this performance. Methods: Six hundred and sixteen (217 female and 399 male) certified Flemish lifeguards (aged 16–71 years) performed BLS with an AED on a Laerdal ResusciAnne manikin simulating an adult victim of drowning. Stepwise multiple linear regression analysis was conducted with BLS/AED performance as outcome variable and demographic data as explanatory variables. Results: Mean BLS/AED performance for all lifeguards was 66.5%. Compression rate and depth adhered closely to ERC 2010 guidelines. Ventilation volume and flow rate exceeded the guidelines. A significant regression model, F (6, 415) = 25.61, p  < .001, ES = .38, explained 27% of the variance in BLS performance (R2 = .27). Significant predictors were age (beta = −.31, p  < .001), years of certification (beta = −.41, p  < .001), time on duty per year (beta = −.25, p  < .001), practising BLS skills (beta = .11, p  = .011), and being a professional lifeguard (beta = −.13, p  = .029). 71% of lifeguards reported not practising BLS/AED. Discussion: Being young, recently certified, few days of employment per year, practising BLS skills and not being a professional lifeguard are factors associated with higher BLS/AED performance. Conclusion: Measures should be taken to prevent BLS/AED performances from decaying with age and longer certification. Refresher courses could include a formal skills test and lifeguards should be encouraged to practise their BLS/AED skills.